Investigation of three pre-treatment methods prior to nanofiltration membrane for palm oil mill effluent treatment - Muhammad Said,; Abdul Wahab Mohammad,; Mohd Tusirin Mohd Nor,; Siti Rozaimah Sheikh Abdullah,; Hassimi Abu Hasan, (Universiti Kebangsaan Malaysia, 2015)
Palm oil mill effluent (POME) treatment has developed in the last decade. Due to the characteristic and volume of POME, it needed a complete treatment to reduce the pollutant content. Three pre-treatments method, ultrafiltration, adsorption and decantation were applied prior to nanofiltration (NF) membrane. The polyethersulphone membrane, montmorillonite as the adsorbent and modern decanter was investigated in this research. Two types of NF membrane, named NF-1 and NF-ASP30 were used after pre-treatment. The removal of four important parameters were determined i.e. COD, TSS, colour and turbidity. The results showed that the adsorption and UF is better than decantation pre-treatment. The ultrafiltration and adsorption can reduce POME content more than 80% for all parameter while decantation varied between 40 and 80%. The combination of ultrafiltration and adsorption with both of NF membrane can removed almost all the parameter. But the decantation can only remove the turbidity but not for the rest of the parameters. Besides the POME content, the flux decline for both of NF membrane was also investigated. The flux of NF-1 membrane was higher than NF-ASP30 membrane but NF-ASP was more relative stable for the flux decline. Overall, NF-1 has better performance in flux decline.